Impact of institutional work on institutional change, boundaries and practices within the creative economy : case: Jyväskylä, Finland - Kovalenko, Oleksiy (2022)
This study aims to explore psychological factors that determine behavioural adap-tive mechanisms (equivocal instances of agency) of the key creative industry actors (cul-tural managers) in creation, maintenance and disruption of cultural institutions in the municipality of Jyväskylä through the lens of “institutional work” theory. Examination of boundaries and practices of key cultural industry institutions (both private and pub-lic) provides additional clue on the state of local creative industry development. Study covers such theoretical frameworks as “institutional work”, “boundary work”, “practice work”, “creative economy”, “creative industry”, “cultural industry” and aims to analyse differences between public and private institutions within the CCI sector in their approach towards institutional change, boundary work and practice work, as well as institutional work. This study provides a unique and novel perspective on the interplay of boundary work and practice work within the creative and cultural industry (CCI).